Diagnosis of pulmonary thromboembolism in the prehospital EMS work: Case report - Uzelac Bojana; Mišić Sanja (ABC: časopis urgentne medicine, 2015)
INTODUCTION: Pulmonary embolism is a condition caused by the obstruction of the small or large branch of the pulmonary artery by a blood clot or other emboli (fat, air, amniotic fluid). Because of the nonspecific symptoms and lack of clinical signs, pulmonary embolism is difficult to diagnose and often remains unrecognized. The aim of this paper is to point out the symptoms and signs that facilitate the diagnosis of pulmonary embolism in the prehospital setting. MATERIALS AND METHODS: We used the data from the medical records of a case report of 72-year-old female patient who is clinically manifested by sudden-onset dyspnea, cyanosis and tachycardia. RESULTS: showed that patient had typical medical history and risk factors (she is a recumbent patient; she was operated because of the hip fracture and discharged from the hospital 2 days ago; already had one episode of pulmonary embolism; obese). Also, she had typical clinical presentation and ECG findings suggestive for pulmonary embolism. The patient was tachycardiac, tachypneic, cyanotic and diaphoretic; she had jugular veins distension; altered sensorium; she was hypotensive-TA: 90/60. On the ECG surface, basic rhythm is an atrial fibrillation, with ventricular transfer about 104 / min; right axis deviation is present; there is a deep S wave in lead I and small q wave with negative T wave in the lead III (S1Q3T3- McGinn-White's sign). RR 'form is present in the V1-V2 (right bundle branch block-RBBB), with deep and negative T wave in leads V1-V3 (sign of the right ventricular systolic overload) with ST depression V3-V6 to 2 mm. These are signs of acute pulmonary heart. They could be transient, but they are typical for massive pulmonary embolism. CONCLUSION: This patient is a classic example of pulmonary embolism, because she had a typical history; the clinical presentation and the ECG changes. Any of the above could facilitate diagnosis or at least get suspicion of pulmonary embolism in the prehospital setting.